STRATEGI YAYASAN SETIA MUDA DALAM PEMBERDAYAAN ANAK MUDA MELALUI KESENIAN MUSIK GAMBANG KROMONG (STUDI DI YAYASAN SETIA MUDA, KELURAHAN CIPEDAK, KECAMATAN JAGAKARSA, KOTA JAKARTA SELATAN) - Dwi Putranto Priyono; Muhtadi Muhtadi (Program Studi Pengembangan Masyarakat Islam (PMI) FIDIKOM, UIN Syarif Hidayatullah Jakarta, 2022)
Setia Muda Foundation is one of the gambang kromong music art studios located in DKI Jakarta Province and has been established since 1995. The studio founded by Mr. Hamdani was built with the aim of empowering young people through their potential, interests and talents. Through several empowerment programs and activities, Setia Muda Foundation has succeeded in producing productive and independent young people. This research is located in Ciganjur Village, Jagakarsa District, South Jakarta City. This research is presented in a descriptive form with a qualitative approach. Sources of data used are primary data derived from observations and interviews, as well as secondary data obtained through the results of several documentation studies, periodic reports, company profiles, transcripts and photos of the implementation of activities. The analysis technique used is data reduction, data presentation and conclusion drawing/verification by triangulation of sources and time. The theory used in this research is the strategy theory proposed by Hatten and Hatten, the theory of empowerment aspects by Kartasasmita, and the theory of empowerment results by Mardikanto and Soebianto. The purpose of this study was to determine the strategy, implementation aspects and results of empowerment by the Setia Muda Foundation for young people through the art of gambang kromong music.